Factors Affecting Healthcare Supply Chain Performance in Tanzania: A Case of Medical Stores Department Headquarters - Geofrey Philemon Mwakasala; Edward Makoye (Journal of International Trade, Logistics and Law)
This study examined factors affecting healthcare supply chain performance in Tanzania. Specifically, the study examined the effect of information technology and inventory control practices on healthcare supply chain performance in Tanzania. The study was conducted in Dar es Salaam region and involved Medical Stores Department (MSD) Headquarters. The study used mixed research approach and a cross-sectional design. Out of 209 populations, 137 respondents were selected as sample size randomly. In data collection, questionnaires and interview were used as tools for collection of data. The study used descriptive and inferential (linear regression) analysis. Findings established that, information technology has positive and statistically significant influence on healthcare supply chain performance. Also, inventory control practices have positive and significant effect on healthcare supply chain performance. The study recommends that, the healthcare sector together with Medical Stores Department (MSD) in Tanzania should consider increasing their investment in information technology infrastructure. This could involve upgrading existing systems, adopting new technologies, and ensuring that IT resources are adequately allocated to support healthcare supply chain operations. Also, healthcare sector and MSD need to ensure seamless integration of different IT systems within and between healthcare organizations. Moreover, MSD should put more emphasis on improving their inventory management systems to ensure that inventory is properly managed and tracked.